2018
DOI: 10.3390/sym10100499
|View full text |Cite
|
Sign up to set email alerts
|

Heat Induction by Viscous Dissipation Subjected to Symmetric and Asymmetric Boundary Conditions on a Small Oscillating Flow in a Microchannel

Abstract: The heat induced by viscous dissipation in a microchannel fluid, due to a small oscillating motion of the lower plate, is investigated for the first time. The methodology is by applying the momentum and energy equations and solving them for three cases of standard thermal boundary conditions. The first two cases involve symmetric boundary conditions of constant surface temperature on both plates and both plates insulated, respectively. The third case has the asymmetric conditions that the lower plate is insula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…(17) and (18) are given: This motion is unsteady and remains unsteady and similar solutions with ramp-type shear stress on the boundary are obtained in [21], eqs. (28) and (29) . The frictional force on the stationary plate and the volume flux, as it results from eqs.…”
Section: F(t) = Th(t) (Ramp-type Shear Stress On the Boundary)mentioning
confidence: 99%
See 1 more Smart Citation
“…(17) and (18) are given: This motion is unsteady and remains unsteady and similar solutions with ramp-type shear stress on the boundary are obtained in [21], eqs. (28) and (29) . The frictional force on the stationary plate and the volume flux, as it results from eqs.…”
Section: F(t) = Th(t) (Ramp-type Shear Stress On the Boundary)mentioning
confidence: 99%
“…For the problem formulated in section Statement of the problem , the energy equation can be written [28,29]:…”
Section: Thermal Transportmentioning
confidence: 99%
“…Nanofluids have modified thermal features compared with the base liquid owing to the existence of solid nano-sized particles [3][4][5][6][7][8] Thus, in order to increase the heat transfer coefficient, nanofluids' utilization in micro and macro channels has been popular. On the other hand, some effects, like viscous dissipation, that can be neglected in macro-scale problems are of particular importance in smaller scales [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is a recent study reviews numerically on the viscous dissipation effect on microchannel flows induced by an oscillatory lower plate [19]. I, it is found that the reported study has missed a set of mixed thermal boundary condition, for which upper boundary insulated and lower with constant surface temperature.…”
Section: Introductionmentioning
confidence: 99%